Using Brunerian Learning Theory with Educational Simulations to Teach Concepts - Laura R. Winer; Richard F. Schmid (Canadian Journal of Learning and Technology, 1986)
The present study maintains that consistently effective leaming materials can best be generated if the prescriptions instructional designers use are founded on learning theory. It is also considered critical that cognitive processes central to the task demands and strategies employed to address them be established. To be practical, we further recommend that only a single, process-oriented lesson, rather than individualized treatment, be implemented. Instructional simulations met these criteria, being tightly bound to Bruner's theoretical approach, and inherently capable of addressing aptitude deficiencies. Subjects were assessed for spatial visualization ability, grouped, randomly assigned to simulation or non-simulation treatments, and tested immediately, one week, and five weeks after instruction. The simulation significantly increased the high-aptitude learners' efficiency (and initially effectiveness), and low-aptitude learners' effectiveness. The validity of a theory-based, aptitude-enhancing, standardized approach was supported, and is discussed.